Penerapan Base Case Method Dalam Pembelajaran Pragmatik Pada Materi Konteks - Fitrianti, Eva; Khairani, Zuraida (STKIP Pesisir Selatan, 2024)
The exploration of pragmatics learning on speech context material using Case Base Method (CBM) is the topic of this research. Explorative qualitative method as a framework to analyze meaningful information about the application of CBM in speech context learning. CBM has advantages and disadvantages that cannot be avoided in the learning process. The advantages are to train students to learn contextually, think critically; solve problems, be able to integrate prior knowledge into cases, develop concepts/ideas; and develop the values of tolerance, respect for other people's opinions, and democracy. Research subjects in the form of students of the Indonesian Language and Literature Education Study Program, Unes registered in the 2024/2025 academic year participated in this study. Data collection used observation, interview, recording, and questionnaire techniques, then analyzed narratively. This study showed that students mastered the concept of context significantly, discussion activation increased, motivation and collaboration developed well, and critical thinking occurred in some students. The challenge for lecturers is to assist students who are passive and must be able to formulate topics and cases that are interesting to students.